Inhibitors in Hemophilia: Treatment Challenges and Novel Options - Barg, Assaf Arie; Livnat, Tami; Kenet, Gili (Seminars in Thrombosis and Hemostasis, 2018)
Hemophilia A (HA) and hemophilia B (HB) are rare congenital severe bleeding disorders, that may be controlled by proper administration of adequate prophylaxis with factor VIII (FVIII), and factor IX (FIX) concentrates, respectively, to prevent joint damage due to recurrent bleeding. However, approximately 30% of patients develop inhibitory antibodies that render factor replacement therapy ineffective. Due to the high variability of patients' bleeding tendency, there is a need to “individually tailor treatment” for this unique group of patients. While replacement therapy with FVIII or FIX can be used for treating HA or HB patients with low responding inhibitors, hemophilia patients with high-responding inhibitors are treated with bypassing agents. Unfortunately, the Bethesda assay applied for inhibitor measurement in most laboratories does not fully predict either bleeding tendency or therapy response. Immune tolerance induction (ITI) may eradicate most inhibitors, yet treatment is challenging during bleeding episodes. The role of bypassing agents and their various treatment strategies still deserves attention. Recently, new nonreplacement therapies have emerged for patients with hemophilia including patients with inhibitors. Adequate monitoring of bypassing therapy and of the new nonreplacement therapies in inhibitor patients is extremely challenging, thus global hemostatic assays are increasingly used to assess clot formation. This review aims to summarize the current treatment and monitoring challenges for inhibitor patients; in this perspective, we will discuss our institutional approach for optimal decision-making and individual therapy tailoring.
Keywords: hemophilia; inhibitors; bypassing agents; immune tolerance; nonreplacement therapy